The Impact of the Omnibus Law on Indonesia's Judicial System: Efficiency or Erosion of Legal Protections? (Indonesian Court and Justice Review, 2025)
The Omnibus Law on Job Creation, enacted in 2020 and amended in 2023, was presented as a transformative reform aimed at streamlining bureaucracy and improving Indonesia’s investment climate. However, its far-reaching legislative changes have also triggered concerns about the erosion of legal protections, including implications for the judicial system. This study critically examines the legal and institutional impact of the Omnibus Law on judicial procedures, labor dispute resolution, and environmental adjudication. Using a doctrinal analysis combined with policy review and expert interviews, the research investigates whether the pursuit of administrative efficiency compromises procedural justice and judicial independence. The findings suggest that while the Omnibus Law reduces regulatory complexity, it also narrows avenues for legal challenge, limits public participation, and accelerates processes in ways that may bypass substantive review. The judiciary’s role is further constrained by shifting legal standards and reduced discretion in certain sectors. The novelty of this research lies in its legal-institutional assessment of judicial capacity post-Omnibus reform. The study contributes to broader debates on deregulation, rule of law, and access to justice in developing democracies. It argues that true efficiency must be balanced with robust safeguards to ensure that economic reforms do not weaken the judiciary’s role as a check on executive and legislative overreach.